Using (TOPSIS) technique for decision-making in Managerial Accounting: A case study - Alyaseer, Ahmad Husain (Journal of Economic, Administrative and Legal Sciences, 2023)
Within its role in decision-making and comparison between the available alternatives, Management Accounting employs multiple standards and uses different data in terms of nature and level of measurement.This research investigates the extent to which Management Accounting can use the TOPSIS, the multi-criteria decision-making technique that is used extensively in engineering sciences, and based solely on mathematical treatments of quantitative data.To achieve this, the research followed a deductive approach, the methodology in which scientific reasoning proceeds from the general to the specific, through the application of general concepts to a realistic case that faced a public sector institution.The results of the research demonstrated the possibility of adopting the TOPSIS technique as a management accounting tool by applying some basics of Data Science.Based on these findings, the research sees the necessity of including the TOPSIS technique and the data transformation tools that were used in the study in the advanced Management Accounting courses.As an additional outcome, the research confirmed that Management Accounting could play in the context of decision rationalization in non-profit organizations the same role it plays in for-profit organizations.
Keywords: Multi-criteria decision; making techniques; TOPSIS Technique; data types; evaluation criteria; Data transformation